2014
DOI: 10.1007/s10439-014-1064-y
|View full text |Cite
|
Sign up to set email alerts
|

Design Modifications and Computational Fluid Dynamic Analysis of an Outflow Cannula for Cardiopulmonary Bypass

Abstract: Cardiopulmonary bypass is a well-established technique during open heart surgeries. However, neurological complications due to insufficient cerebral oxygen supply occur and the severe consequences must not be neglected. Recent computational fluid dynamics (CFD) studies showed that during axillary cannulation the cerebral perfusion is strongly affected by the distance between the cannula tip and the vertebral artery branch. In this study we use two modifications of the cannula design to analyze the flow charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…A study using an in vitro model of human AVG reported directional vorticity of ±550 1/s at the AVG anastomosis [31], and a CFD simulation of intracranial arterial aneurysms reported directional vorticity of -1000 to +1600 1/s [12]. In addition, in a CFD analysis of blood flow in an outflow cannula for cardiopulmonary bypass, helicity magnitude was reported up to 1.5x10 5 cm/s 2 [13]. Increasing positive values of Q-criterion (indicating vortices) have been reported in a CFD model of arterial stenosis, with greater regions of positive Q-criterion throughout the artery volume as the stenosis becomes more constrictive [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study using an in vitro model of human AVG reported directional vorticity of ±550 1/s at the AVG anastomosis [31], and a CFD simulation of intracranial arterial aneurysms reported directional vorticity of -1000 to +1600 1/s [12]. In addition, in a CFD analysis of blood flow in an outflow cannula for cardiopulmonary bypass, helicity magnitude was reported up to 1.5x10 5 cm/s 2 [13]. Increasing positive values of Q-criterion (indicating vortices) have been reported in a CFD model of arterial stenosis, with greater regions of positive Q-criterion throughout the artery volume as the stenosis becomes more constrictive [14].…”
Section: Discussionmentioning
confidence: 99%
“…Comparing these previous findings to our work, we find that similar vorticity was seen in our mouse AVF in 4 mm averages (349 ± 768 1/s at Day 21) compared to human AVF and AVG in the vein (550-1600 1/s) [12, 31]. In our mouse AVF vein at Day 21, we calculated increased helicity (96.4 ± 5460 cm/s 2 ) and positive Q-criterion (1.21 ± 100×10 3 1/s 2 ) when compared to non-surgery veins, indicating helical, disturbed flow, and the formation of vortices in the AVF veins, as seen in vascular studies of helical, disturbed flow in cannulated cardiopulmonary bypass and arterial stenosis [13, 14, 32]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Howbeit, internal structure manipulation in the latter case showed outflow pattern improvements, it is suspicious to thrombosis and hemolysis due to flow disturbance and stagnation caused by internal stator. Furthermore, an internal profile alteration for spiral flow generation produces less area for the blood flow which can result in a higher internal velocity, and therefore, higher shear stresses. A recent study proposed to use an inlet chamber to induce spiral jet flow which was reported to reduce the impinging velocity by 21%.…”
Section: Introductionmentioning
confidence: 99%
“…Plastic cannulae have been developed for use in other fields of medicine such as ventricular assist devices , cardiopulmonary bypass , and central venous catheters . The outcomes of these developments have resulted in an optimized geometry of the tip and side holes as well as improved placement in the respective blood vessel to reduce the risk of thrombus formation.…”
mentioning
confidence: 99%